The pursuit of perfect : how to stop chasing perfection and start living a richer, happier life - Ben-Shahar, Tal (HighBridge Audio, 2009)
Ben-Shahar takes us off the impossible pursuit of perfection and directs us to the way to happiness, richness and true fulfillment. He shows us freedom derived from not trying to do it right all the time and the real lessons that failure and painful emotions can teach us.